Anti-fading technology of near space communication based on quasi-constant envelope OFDM - Yang LU; Donglei ZHANG; Tingting WANG (Dianxin kexue)
For the near space high altitude platform station (HAPS), its limited power, tight spectrum resources, and the multipath fading effects due to non line of sight (NLoS) and low elevation communication environment are the main problems. An anti-fading technology of near space communication based on quasi-constant envelope OFDM (QCE-OFDM) was proposed. At the transmitting end, two OFDM signals were respectively modulated on the phases of two constant envelope signals, and then they were merged into one signal via phase shift. At the receiving end, Taylor series expansion technology was employed to divide and demodulate the signal. Analysis and simulation results show that the QCE-OFDM has the same spectral efficiency as OFDM. By selecting the modulation index reasonably, the proposed scheme can combat multipath fading effectively with less than 3 dB signal peak-to-average power ratio (PAPR), where the goal of high spectral efficiency and high energy efficiency can be achieved.